ISOLASI DAN PEMANFAATAN BAKTERI KITINOLITIK DARI CANGKANG UDANG PUTIH (PENAEUS MERGUENSIS) DALAM MENGHASILKAN ENZIM KITINASE - Nin Suharti; Halimah Fitriani (Poltekkes Kemenkes Medan, 2023)
Indonesia is listed as the third largest shrimp producing country in the world. Shrimp is one of the leading export commodities. Shrimp is one of the main commodities in the fishing industry. Thus encouraging Indonesia to become one of the shrimp producing countries. In the shrimp processing process, usually the heads and shells of the shrimp are thrown away or used as animal feed. Traditionally, shrimp shell waste is generally used as a mixture for making crackers, paste, shrimp paste and as additional animal feed and returned to the shrimp cultivation itself. One use of shrimp shell waste that has prospects for development and has quite high economic value is processing it into chitin, chitosan and glucosamine. The aim of this research is to obtain isolates of chitinolytic bacteria from isolation and to utilize chitinolytic bacteria from white shrimp (Penaeus merguensis) shells to produce chitinase enzymes. Chitinolytic bacteria are bacteria that produce chitinase enzymes which play a role in degrading chitin into oligomers and chitin derivative compounds. Chitinolytic bacteria can be obtained from various sources such as the rhizosphere, phyllosphere, soil or from water environments such as seas, lakes, ponds or shrimp ponds and so on. Chitin that exists in nature is easily degraded by microorganisms. There are two pathways in the chitin degradation process. First, degradation by chitinolytic which hydrolyzes the ?-1,4-glycoside bond. Second, the polymer undergoes first deacetylation and then hydrolysis by chitosanase. Chitinase has many benefits, including as a bioinsecticide and biofunctional agent in controlling plant pests and is used to process chitin waste in the shrimp and crab freezing industry. It can also be used in the medical and food fields. From the test results, three types of bacteria were obtained, namely Vibrio sp, Bacillus sp, and Pseudomonas sp.